Culture of Abuse of Power in Indonesia from the Perspective of Criminology and Law - Slamet Riyadi, Bambang (2022)
The cultural anatomy of abuse of power in Indonesia from the perspective of criminology and law impacts deviant actions not only in the depressions of power and moral behavior of public officials. In fact, many public officials abuse of power is performed by being corrupt or punished, even by severe law, even the perpetrators of power abuses continue corruption or it can be seen that there is no clear effects for corruptors. However, it is a wrong system in the life of nation and state, when public officials who depart from the people do not have a view of life as a nation and state as they should. Therefore, according to the views and suggestions of the author, this nation and country need to return to a system of joints of the life of the nation and state of Indonesia, that is carrying out the points of practice and appreciation of the precepts of the Pancasila with the truth not just mere rhetoric, because the state ideology of Pancasila has been built since the country was founded by the founding father